Limited Effects of Ultra-low Oxygen Concentration during Extended Embryo Culture on In vitro Fertilisation Outcomes in Indian Women: A Retrospective Cross-sectional Study - Deven Patel; R. G. Patel; Trupti Patel; Nikunj Patel; Naroda Maheshwari (Journal of Human Reproductive Sciences)
Background: Amongst various other factors, oxygen (O2) concentration in embryo culture plays an important role in determining pregnancy outcomes in women undergoing in vitro fertilisation. Some studies have reported that lowering O2 levels in embryo culture provides better results. Aims: To explore the effects of low- and ultra-low- O2 concentrations (5% and 2%, respectively) in extended embryo culture on various outcome parameters of pregnancy. Settings and Design: This was a retrospective cross-sectional study. Materials and Methods: In this study 382 participants had their embryos cultured in varying O2 concentrations (5% or 2%), followed by either a fresh embryo transfer (ET) or frozen embryo transfer (FET). Outcomes such as pregnancy rate, implantation rate, abortion rate, twinning rate, and live birth rate were compared between the groups. Statistical Analysis Used: Chi square test was applied to compare the primary and secondary outcomes between different groups. Results: No significant differences were observed in pregnancy rate and implantation rate between 5% and 2% O2 groups, irrespective of their mode of ET. The abortion rate was significantly higher in 5% O2 group than in 2% group during FET (24.71% vs. 11.49%, P = 0.02). While the proportion of good-quality embryos was higher in 5% O2 group, these did not translate to better pregnancy outcomes. Additionally, embryos cultured in 2% O2 concentration had a significantly better implantation rate when they were transferred fresh rather than frozen (71.34% vs. 61.46%, P = 0.04). There were no other differences observed. Conclusion: Only marginal benefits were observed in switching human embryos to ultra-low O2 concentration after the initial days of culture.